Ludwig's angina associated with mediastinal complications: Case report (Research, Society and Development, 2020)
Ludwig's angina, considered a medical emergency, is an infection that affects the submandibular, sublingual, and submental spaces, presenting a course of rapid and potentially fatal evolution. The purpose of this report is to describe the treatment of a case of Ludwing's Angina, due to dental infection, associated with cervicofacial and mediastinal complications. The female patient appeared with a history of increased volume in the region in the bilateral and submental submandibular region, complaints of dysphagia, and dyspnea, in addition to trismus. The patient was initially treated employing drainage and extraction of the element that caused the infection, 72 hours after the operation, however, the patient returned to dyspnea. For the treatment of this complication, there was the option to perform cervicotomy associated with broad-spectrum antibiotic therapy. The therapeutic approach containing airway maintenance, cervicotomy, antibiotic therapy, as well as the removal of the etiological factor was effective for the management of this case of Ludwing's angina complication.